Lifecycle BIM for Infrastructure: A Business Case for Project Delivery and Asset Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Building Information Modeling (BIM) allows transportation infrastructure project teams to improve the overall quality of the planning and design of projects as well as more efficiently construct the project through improved planning, cost control, and automation, such as machine-guided equipment.The TRB Cooperative Research Program's CRP Special Release 4: Lifecycle BIM for Infrastructure: A Business Case for Project Delivery and Asset Management focuses on the development of resources to support the adoption of BIM by highway agencies. Supplemental to the report are an assessment matrix for Appendix E: BIM Maturity Matrix for Transportation Agencies, BIM multi-media materials, and video interviews.
Keywords: Transportation and Infrastructure

Beyond Compliance: Strengthening the Safety Culture of the Offshore Oil and Gas Industry - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Beyond Compliance: Strengthening the Safety Culture of the Offshore Oil and Gas Industry summarizes recommendations to industry and regulators to strengthen and sustain the safety culture of the offshore oil and gas industry.The committee that prepared the report addresses conceptual challenges in defining safety culture, and discusses the empirical support for the safety culture definition offered by the Bureau of Safety and Environmental Enforcement, the nine characteristics or elements of a robust safety culture, methods for assessing company safety culture, and barriers to improving safety culture in the offshore industry.The committee’s report also identifies topics on which further research is needed with respect to assessing, improving, and sustaining safety culture. Download the full report issued in May 2016 or a Report in Brief.
Keywords: Transportation and Infrastructure

Use of Vehicle Probe and Cellular GPS Data by State Departments of Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Over the last decade, state departments of transportation (DOTs) have begun to use vehicle probe and cellular GPS data for a variety of purposes, including real-time traffic and incident monitoring, highway condition, and travel demand management. DOTs are also using vehicle probe and cellular GPS data to inform system planning and investment decisions.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 561: Use of Vehicle Probe and Cellular GPS Data by State Departments of Transportation documents how DOTs are applying vehicle probe and cellular GPS data for planning and real-time traffic and incident monitoring and communication.In December 2021, an erratum was issued.
Keywords: Transportation and Infrastructure

Entrained Air-Void Systems for Durable Highway Concrete - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Laboratory testing and field experience have shown that highway concrete should be properly air entrained to resist the action of freezing and thawing, particularly in wet climates. Several gaps in the state of the knowledge still exist.The TRB National Cooperative Highway Research Program's NCHRP Research Report 961: Entrained Air-Void Systems for Durable Highway Concrete addresses these gaps and, more specifically, investigates innovative test methods for effectively characterizing the air system in fresh concrete and identifying the characteristics of the air-void system that are related to the performance of field concrete under freeze-thaw conditions.Appendices A –G provide further details on the different aspects of the research performed for this project.• Appendix A: Test: Matrix for Laboratory Mixtures• Appendix B: Petrographic Analysis Report• Appendix C: Appendix C Data Obtained from Testing Concrete Mixtures Produced in the Laboratory• Appendix D: Appendix D Flatbed Scanner Threshold Optimization Details and Test Results• Appendix E: Clustering Analysis Test Results• Appendix F: Microcomputer Control for AASHTO T 161 “A” Freeze–Thaw• Appendix G: Data Obtained During F-T Testing
Keywords: Transportation and Infrastructure

Air Quality in Transit Buses - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
With a major drop in U.S. transit ridership since the start of the COVID-19 pandemic, an increased understanding of infectious disease in confined spaces and the role of droplets and particles in transmission has been increasingly important to the bus industry. A combination of experiments, models, and simulations in fluid dynamics has been employed to understand how aerosols move in spaces containing people. TRB's Transportation Insights 2: Air Quality in Transit Buses provides a summary of a June 2022 in-person TRB Transit Cooperative Research Program (TCRP) Insight Event.
Keywords: Transportation and Infrastructure

Urban Air Mobility: An Airport Perspective - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Urban Air Mobility (UAM), or its generalized version, Advanced Air Mobility (AAM), is an emerging aerial transportation approach that involves the operation of highly automated aircraft for a safe and efficient system to transport passengers or cargo at lower altitudes of airspace within urban, suburban, and exurban areas. UAM initiatives are advancing in many communities and will likely bring many societal changes.The TRB Airport Cooperative Research Program's ACRP Research Report 243: Urban Air Mobility: An Airport Perspective provides a comprehensive examination of the emerging UAM industry, with a particular focus on its impacts and opportunities for airports.Supplemental to the report are an Airport AAM Preparation Checklist and a UAM Airport Assessment Toolkit.
Keywords: Transportation and Infrastructure

Integrating Airport Geographic Information System (GIS) Data with Public Agency GIS - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Synthesis 59: Integrating Airport Geographic Information System (GIS) Data with Public Agency GIS identifies effective and emerging data exchange practices that airports and public agencies can use to increase the data they have access to, while reducing the cost of identifying, collecting, and maintaining these data. It synthesizes the need expressed by airports and public agencies to exchange geographic information and related resources, highlighting effective practices and industry trends.
Keywords: Transportation and Infrastructure

Assessing Air Pollution Dispersion Models for Emissions Regulation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
State departments of transportation (DOTs) conduct project-level air quality analyses to comply with the National Environmental Policy Act and meet transportation conformity rule requirements where applicable. DOTs are interested in a rigorous and systematic model review and update process for regulatory dispersion models to ensure the models generate credible results. NCHRP Research Report 1058: Assessing Air Pollution Dispersion Models for Emissions Regulation, from TRB's National Cooperative Highway Research Program, presents state-of-the-art methods and analytical approaches for project-level air quality modeling by reviewing eight air quality models in use for transportation project analyses. Supplemental to the report are Appendix A, Appendix B, Appendix C, Appendix D, Appendix E part 1a, Appendix E part 1b, Appendix E part 1c, Appendix E part 2, Appendix F, Appendix G, and a PowerPoint presentation of the research results.
Keywords: Transportation and Infrastructure

Airport-Centric Advanced Air Mobility Market Study - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Advanced air mobility (AAM) is a broad concept enabled by new technology with the potential to transform aviation and urban transportation systems over the next 10 years. Some of these technologies include electric vertical takeoff and landing (eVTOL) aircraft as well as traditional fixed-wing aircraft using electric or other advanced propulsion systems. ACRP Synthesis 130: Airport-Centric Advanced Air Mobility Market Study, from TRB's Airport Cooperative Research Program, is designed to help airports and other stakeholders as they plan for AAM. Many of the initial use cases for AAM will be integrated into existing airports of all sizes, including airport ground access, connecting passenger service between regional and hub airports, and cargo operations.
Keywords: Transportation and Infrastructure

Application of Big Data Approaches for Traffic Incident Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Big data is evolving and maturing rapidly, and much attention has been focused on the opportunities that big data may provide state departments of transportation (DOTs) in managing their transportation networks. Using big data could help state and local transportation officials achieve system reliability and safety goals, among others. However, challenges for DOTs include how to use the data and in what situations, such as how and when to access data, identify staff resources to prepare and maintain data, or integrate data into existing or new tools for analysis. NCHRP Research Report 1071: Application of Big Data Approaches for Traffic Incident Management, from TRB's National Cooperative Highway Research Program, applies the guidelines presented in NCHRP Research Report 904: Leveraging Big Data to Improve Traffic Incident Management to validate the feasibility and value of the big data approach for Traffic Incident Management (TIM) among transportation and other responder agencies. Supplemental to the report are Appendix A through Appendix P, which detail findings from traditional and big data sources for the TIM use cases; a PowerPoint presentation of the research results; and an Implementation Memo.
Keywords: Transportation and Infrastructure

BIM Beyond Design Guidebook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The complexity of airport management has grown dramatically in recent years, with increased security requirements, a focus on sustainability, increased competition, new technologies, and traffic growth.The TRB Airport Cooperative Research Program's ACRP Research Report 214: BIM Beyond Design Guidebook gives airport owners the basic knowledge required to manage this complexity through building information modeling (BIM), a practice that has transformed the design and construction industry over the last decade and is now emerging as a key component to enhancing an asset life cycle management approach for many organizations.
Keywords: Transportation and Infrastructure

Practices for Project-Level Analyses for Air Quality - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The nature of the transportation project-level air quality arena is evolving, and there are potentially significant impacts to project schedules and budgets should air quality issues arise.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 576: Practices for Project-Level Analyses for Air Quality compiles and documents information regarding existing practices related to project-level air quality analysis by state departments of transportation (DOTs).Also included as part of the report are a survey on project-level air quality in Appendix A and the survey's findings in Appendix B.
Keywords: Transportation and Infrastructure

Modernizing the U.S. Offshore Oil and Gas Inspection Program for Increased Agility and Safety Vigilance - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Bureau of Safety and Environmental Enforcement (BSEE), in seeking to augment and improve its offshore oil and gas inspection program, should focus less on inspecting all oil platforms and become more outcome-based by focusing on the riskiest entities.These are among the findings in TRB Special Report 338: Modernizing the U.S. Offshore Oil and Gas Inspection Program for Increased Agility and Safety Vigilance, from the Transportation Research Board of the National Academies of Sciences, Engineering, and Medicine.Given the expectation that it inspect each offshore facility at least once per year, BSEE faces many challenges as it seeks to fulfill its stated mission “to promote safety, protect the environment, and conserve resources through vigorous regulatory oversight.” Although BSEE has taken a number of initiatives to meet these challenges, it faces many constraints and will need to make many strategic-level choices to innovate and evolve its inspection program to keep pace with the continually changing offshore energy landscape.
Keywords: Transportation and Infrastructure

Long-Term Infrastructure Program Letter Report: January 23, 2018 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Committee for the Review of Federal Highway Administration (FHWA) Infrastructure R&D Program has issued its first Long-Term Infrastructure Program (LTIP) letter report. The first meeting was structured around a series of briefings on the two components of the LTIP: the Long-Term Pavement Performance (LTPP) program and the Long-Term Bridge Performance (LTBP) program. The charge to the committee is to “advise the Federal Highway Administration (FHWA) Infrastructure R&D Program regarding priorities in terms of the technical tools and products that state departments of transportation need to maintain and improve the performance of their pavements, bridges, and other structures.” The committee was established to provide an ongoing review of the LTIP based on annual meetings with FHWA staff and stakeholders. The committee will issue an annual letter report with its recommendations on priorities for the LTIP.
Keywords: Transportation and Infrastructure

Evaluation of the Exploratory Advanced Research Program - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Beginning in 2019, the U.S. Federal Highway Administration (FHWA) requested that TRB be directly involved in managing evaluations of selected projects undertaken by the agency. The TRB Cooperative Research Program's CRP Special Release 2: Evaluation of the Exploratory Advanced Research Program presents an evaluation of the program, which works on a range of topics, including human-automation interaction, safety improvements through advanced data analysis, innovative materials for highway pavements and structures, methods to improve transportation system resilience, and technologies for alternative fuels development.
Keywords: Transportation and Infrastructure

Evaluation of Ultra-High Performance Concrete Connections - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Beginning in 2019, the U.S. Federal Highway Administration (FHWA) requested that TRB be directly involved in managing evaluations of selected projects undertaken by the agency. The TRB Cooperative Research Program's CRP Special Release 3: Evaluation of Ultra-High Performance Concrete Connections presents an evaluation of the UHPC Research and Development Program. UHPC is used in highway bridges, particularly for bridge-deck-level connections for prefabricated bridge elements.
Keywords: Transportation and Infrastructure

Measuring and Understanding the Relationship Between Air Service and Regional Economic Development - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Airport economic impact studies may accurately measure the activity that occurs on airport properties or is tied directly to airport operations (such as off-site parking and hotels that accommodate airline crew who overnight in a location), but they do not capture how air service supports business and employment throughout the region. The TRB Airport Cooperative Research Program's ACRP Web-Only Document 53: Measuring and Understanding the Relationship Between Air Service and Regional Economic Development provides airports and major regional stakeholders concerned with economic development with the information and tools necessary to understand and communicate the nexus between air service and regional employment. The Web-Only Document is supplemental to ACRP WebResource 12: Air Service Development and Regional Economic Activity. Supplemental to the Web-Only Document is a Case Study Compilation with the full versions of the 14 case studies performed as part of the project.
Keywords: Transportation and Infrastructure

Advanced Air Mobility and Community Outreach: A Primer for Successful Stakeholder Engagement - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Advanced Air Mobility (AAM) includes the use of new aircraft technologies to transport passengers and cargo, typically on demand. The AAM ecosystem will initially rely on existing airports, heliports, and routes, but in the future, new dedicated facilities and routes will likely be developed. The impacts of AAM may be far-reaching and affect many stakeholders. ACRP Research Report 261: Advanced Air Mobility and Community Outreach: A Primer for Successful Stakeholder Engagement, from TRB's Airport Cooperative Research Program, offers strategies and tools to help airport operators encourage and promote engagement with AAM operators, government agencies, and communities. Supplemental to the report is Appendix C: Stakeholder Engagement Toolkit.
Keywords: Transportation and Infrastructure

Using GIS for Collaborative Land Use Compatibility Planning Near Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Research Report 200: Using GIS for Collaborative Land Use Compatibility Planning Near Airports offers guidance for using Geographic Information Systems (GIS) as a collaboration tool to encourage compatible land use around airports.The report is designed to help airport and community planners seeking to work together to protect existing and future airport development as well as maintain safety and improve quality of life for those living and working near airports.The report includes a description of the perspectives, goals, responsibilities, and concerns of the federal government, airports, and local communities to ensure that each has a good understanding of the others’ missions and priorities. The report also examines potential benefits that GIS might have on fostering collaboration and offers guidance on initiating and maintaining collaboration, and for developing, sharing, and using data.A key feature of the guidebook is examples of how GIS was used collaboratively to address various land use compatibility issues, including aircraft noise, obstructions, wildlife hazards, and solar glare. A set of appendices supplements the guide by summarizing the role of government, providing a brief history of FAA aeronautical surveys, case studies, and example data sharing agreements.Presentation templates for stakeholder outreach on noise and obstruction, as well as a sample outreach flier on the value of GIS in airport planning, were produced as part of this project.
Keywords: Transportation and Infrastructure

Guidebook on Integrating GIS in Emergency Management at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s Airport Cooperative Research Program (ACRP) Report 88: Guidebook on Integrating GIS in Emergency Management at Airports is designed to help airports identify needs and assess current capabilities with respect to using geographical information systems (GIS) in emergency management (EM).The report discusses GIS and emergency management and provides a roadmap for airports to move from their current state of GIS implementation (even if they do not yet have any form of GIS) to the point of integrating into emergency management and coordinating with mutual aid partners.The guidebook contains a CD-ROM with case studies and key lessons learned from airports that have integrated GIS into EM. The guidance concludes with a checklist of how to maintain and keep EM plans relevant and current.The project that developed ACRP Report 88 also produced a PowerPoint presentation that outlines the benefits of integrating GIS into EM, which is also available on the CD-ROM.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure